1989
DOI: 10.1021/jm00128a003
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterials. Synthesis and structure-activity studies of 3-aryl-2-oxooxazolidines. 1. The B group

Abstract: The synthesis and structure/activity studies of the effect of varying the "B" group in a series of oxazolidinone antibacterials (I) are described. Two synthetic routes were used: (1) alkylation of aniline with glycidol followed by dialkyl carbonate heterocyclization to afford I (A = H, B = OH), whose arene ring was further elaborated by using electrophilic aromatic substitution methodology; (2) cycloaddition of substituted aryl isocyanates with epoxides to give A and B with a variety of values. I with B = OH o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
69
0
3

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(77 citation statements)
references
References 2 publications
5
69
0
3
Order By: Relevance
“…Concerning the lipophilicity on oxazolidinones, it has been reported that the balance between 5-hydrophilic substituent and hydrophobic substituent on the aromatic ring is important for the antibacterial activity. 2,4) In this paper, we describe our SAR study, especially the relationship between lipophilicity and antibacterial activity, on (4Ј-cycloalkylamino)phenyl oxazolidinones bearing 5-thiocarbonyl groups.Chemistry 5-Thiourea oxazolidinones 4 and 5-dithiocarbamate oxazolidinones 5 were synthesized as shown in Chart 2. They were prepared from key intermediates 12, which were easily derived from 6 by the usual method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the lipophilicity on oxazolidinones, it has been reported that the balance between 5-hydrophilic substituent and hydrophobic substituent on the aromatic ring is important for the antibacterial activity. 2,4) In this paper, we describe our SAR study, especially the relationship between lipophilicity and antibacterial activity, on (4Ј-cycloalkylamino)phenyl oxazolidinones bearing 5-thiocarbonyl groups.Chemistry 5-Thiourea oxazolidinones 4 and 5-dithiocarbamate oxazolidinones 5 were synthesized as shown in Chart 2. They were prepared from key intermediates 12, which were easily derived from 6 by the usual method.…”
mentioning
confidence: 99%
“…Pharmacia group found linezolid (2) 3) which was known to be the first candidate of effective oxazolidinones against serious gram-positive human pathogens caused by methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococci (VRE) without severe toxicity.…”
mentioning
confidence: 99%
“…The oxazolidinones, exemplified by Dup-721 (1), 1) are an exciting new class of synthetic antibacterial agents and are reported to be effective against staphylococci, streptococci and enterococci.…”
mentioning
confidence: 99%
“…6) Concerning the 5-substituent on the oxazolidinone ring, Dupont's group reported that the 5-hydroxymethyl or the 5-halogenomethyl group had weak antibacterial activities against gram-positive bacterial strains. 7) Furthermore, Gregory et al 1) concluded that the acetylaminomethyl moiety was the best substituent at the 5-position on oxazolidinone, in consequence of their SAR study. But their effort was mainly limited to carbonyl functionalities.…”
mentioning
confidence: 99%
“…Oxazolidinone antibacterial agents 2) are a new class of synthetic antibacterial agents with activity against gram-positive bacteria. Their mode of action has been found to inhibit the protein synthesis in the initial stage.…”
mentioning
confidence: 99%